2018
DOI: 10.1016/j.solmat.2017.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bulk effects of K in Cu1−xKxIn1−yGaySe2 solar cells

Abstract: Two strategies for enhancing photovoltaic (PV) performance in chalcopyrite solar cells were investigated: Cu1-xKxIn1-yGaySe2 absorbers with low K content (K/(K+Cu), or x ~ 0.07) distributed throughout the bulk, and CuIn1-yGaySe2 absorbers with KIn1-yGaySe2 grown on their surfaces. For the Ga-free case, increased temperature improved PV performance in the KInSe2 surface absorbers, but not in the bulk x ~ 0.07 absorbers.Growth temperature also increased KInSe2 phase fraction, relative to Cu1-xKxInSe2 alloys-evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…Overall, the K integration throughout the CKIS absorber and the application of a KIS surface both improve the final CuInSe 2 device. While Ga was excluded from the present study for simplicity, the present growth strategies for K incorporation were confirmed for Ga‐containing alloys up to Ga/(Ga + In) of 0.5 in another study . However, that study and another using RbF PDTs found little or no benefits for CuGaSe 2 …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Overall, the K integration throughout the CKIS absorber and the application of a KIS surface both improve the final CuInSe 2 device. While Ga was excluded from the present study for simplicity, the present growth strategies for K incorporation were confirmed for Ga‐containing alloys up to Ga/(Ga + In) of 0.5 in another study . However, that study and another using RbF PDTs found little or no benefits for CuGaSe 2 …”
Section: Resultssupporting
confidence: 55%
“…The diverse absorber/buffer interface effects have impeded consensus regarding the true efficiency enhancing nature of the KF PDT, and a controlled experiment is needed to elucidate these issues. Alternative processing approaches have been used to develop Cu 1‐x K x InSe 2 alloys and Cu 1‐x K x In 1‐y Ga y Se 2 to better understand the KF PDT, particularly the materials chemistry of K in CIGS solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting observations are coherent with the conclusions from previous sections: the subtsitution of copper with alkali metals widens the band gap of the materials studied. This finding is, in general, in good agreement with the experimental data available (notably for the substitution of Cu by Li and K in CuInS 2 and CuInSe 2 or Rb in CuInSe 2 ) and with other theoretical works: , the error in the calculated band gap values does not exceed 10%. A recent study accounts for the band gap widening of RbInSe 2 in comparison to CuInSe 2 , according to both experiment and theory.…”
Section: Resultssupporting
confidence: 91%
“…The passivation efforts heal the defects in the absorber bulk and at the absorber/buffer, absorber/back contact interfaces. [ 112–114 ] The defect passivation improves bulk carrier lifetime and diffusion lengths. [ 115 ] Nadenau et al reported the V oc improvements for Na‐containing Ga‐rich CGSe, and Ishizuka et al reported the J sc improvements for PDT‐RbF‐treated CGSe devices.…”
Section: Cgse Solar Cell's Architecture and Performance‐limiting Factorsmentioning
confidence: 99%